Patient-Related Outcomes of Arthroscopic Resection of Ganglion Cysts of the Wrist - d'Ailly, Philip N.; Koopman, Jaimy E.; Selles, Caroline A.; Rahimtoola, Zulfiquar O.; Schep, Niels W.L. (Journal of Wrist Surgery, 2020)
Background Ganglion cysts of the wrist can cause pain and loss of functionality. No consensus exist on optimal treatment. Arthroscopic resection shows promising results but is poorly studied. Furthermore, only few studies have used patient-related outcomes to evaluate arthroscopic treatment.Purpose The purpose of this study was to assess patient-related outcomes following arthroscopic resection of wrist ganglion cysts.Patients and Methods This was a retrospective study of all consecutive patients that underwent arthroscopic resection of a dorsal or volar wrist ganglion. Minimum follow-up was 6 months. The primary outcome was the patient-rated wrist evaluation (PRWE). Secondary outcomes were recurrence rate and complications.Results A total of 53 patients were included with a mean follow-up of 13 months (interquartile range: 6–23 months). Twenty-six patients (49%) presented with a recurrence following prior treatment. Mean PRWE was 13 (standard deviation [SD] = 1.8), with no difference between patients with dorsal or volar ganglion cysts. There were five recurrences (9%), of which three occurred in the first five patients who were operated. There were three patients with complications (6%), consisting of neuropraxia, extensor carpi ulnaris tendinitis, and painful scar tissue.Conclusion Arthroscopic resection results in good patient-related outcome and low complication and recurrence rates when performed by an experienced surgeon. Recurrence and complication rates are similar to arthroscopic resections described in literature and superior to open resection and needle aspiration. Well-designed randomized clinical trials will be necessary to confirm these findings.Level of Evidence This is a level IV, retrospective study.
Keywords: wrist; arthroscopy; ganglion cyst; patient outcome; complications; PRWE